So Distant, almost Close (diségno, 2021)
IntroductionIt was with some hesitation that I initially accepted the invitation extended to me by my friend and colleague Francesca Fatta to reflect on the theme of Drawing: distances, languages, technologies during the opening of the Study Day organized by UID (Italian Union for Drawing) and held online on September 18, 2020. The three (actually four) terms evoked in the title of the Seminar correspond to the same number of existential and experiential categories that, never as in these months of pandemic, have taken on ambiguous and contradictory meanings, previously unimaginable. The physical (but not social) distancing has forced us to reflect on how important proximity is for the human race and how by now this can/should be expressed not only through in-person contact, but also mediated by other communicative structures, all focused on the visual, but unable to solicit in us a satisfactory overall response of mirror neurons, and to act in the synesthetic field on all our senses ... [read more]